Corrosion Behavior Analysis of Novel Sn-2.5Ag-1.0Bi-0.8Cu-0.05Ni and Sn-1.8Bi-0.75Cu-0.065Ni Pb-Free Solder Alloys via Potentiodynamic Polarization Test - Sang Hoon Jung; Jong-Hyun Lee (Metals)
The corrosion behaviors of newly developed solder alloys with excellent mechanical properties, Sn-2.5 Ag-1.0 Bi-0.8 Cu-0.05 Ni (SABC25108N) and Sn-1.5 Bi-0.75 Cu-0.065 Ni (SBC15075N), are analyzed to supplement the corrosion behavior of the limited corrosion data in Pb- and Zn-free solder compositions. A potentiodynamic polarization test is conducted on these compositions in a NaCl electrolyte solution, the results of which are compared with those of conventional Sn-3.0 (wt%) Ag-0.5Cu and Sn-1.2Ag-0.5Cu-0.05Ni alloys. The results indicate that SBC15075N exhibits the lowest corrosion potential and highest corrosion current density, thus signifying the lowest corrosion resistance. By contrast, SABC25108N exhibits the lowest corrosion current density and highest corrosion resistance. Notably, SABC25108N shows a slower corrosion progression in the active state and exhibits the longest passive state. The difference in corrosion resistance is affected more significantly by the formation and distribution of the Ag3Sn intermetallic compound phase owing to the high Ag content instead of by the presence of Bi or Ni. This uniform dispersion of Ag3Sn IMC phases in the SABC25108N alloy effectively suppressed corrosion propagation along the grain boundaries and reduced the formation of corrosion products, such as Sn3O(OH)2Cl2, thereby enhancing the overall corrosion resistance. These findings provide valuable insights into the optimal design of solder alloys and highlight the importance of incorporating sufficient Ag content into multicomponent compositions to improve corrosion resistance.